(untitled) (Semiárida, 2020)
For the purpose of obtaining a partial Knowledge of the forage importance of some xerophytes specimens that grow in the Shouth West of the province of La Pampa and are browsed by cattle an investigation of the contente of the crude protein, calcium, magnesium, and phosphorus was affected during a year. Therefore, samples of the eaten parts of trees, shrubs and sub-shrubs were taken approximately every 2 months and analysis made of the previously mentionated elements. The majority of the specimens have a 10% and more of PB. They are also good contributors of Ca, Mg and P. Except P the contents vary due to rain and time of the year.